2011
DOI: 10.1590/s0102-86502011000700007
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with oil mixes of high ratio Omega-9: Omega-6 and a low ratio Omega-6:Omega-3 in rats subjected to brain ischemia/reperfusion

Abstract: PURPOSE: This study aimed to assess the effects of preconditioning with mixtures of oils containing high/low ratio of ω-6/ω-3 and ω-9/ω-6, respectively, in an experimental model of cerebral ischemia-reperfusion (I/R). METHODS: Forty-two Wistar rats were randomly distributed into two groups: control (n=24) and test (n=18). Control group was subdivided in 4 subgroups (n=6): G1: Sham-Water; G2: I/R-Water; G3: Sham-Isolipidic and G4: I/R-Isolipid. The animals received water or a isolipid mixture containing ω-3 oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Pinheiro and cols in 2011, have shown that the preconditioning of 42 male rats with different omega oil mix preparations promoted protection against the deleterious effects of ischemia/reperfusion injury demonstrated by the reduction of red neurons in the group that received mix 2 (omega 6: omega 3 ratio-1.4:1; omega 9: omega 6 ratio-3.4:1) source of omega 3 ALA (35%) + EPA (39%) + DHA (26%) [39].…”
Section: Use Of Omega 3 6 and 9 In Brain Ischemia Animal Modelsmentioning
confidence: 99%
“…Pinheiro and cols in 2011, have shown that the preconditioning of 42 male rats with different omega oil mix preparations promoted protection against the deleterious effects of ischemia/reperfusion injury demonstrated by the reduction of red neurons in the group that received mix 2 (omega 6: omega 3 ratio-1.4:1; omega 9: omega 6 ratio-3.4:1) source of omega 3 ALA (35%) + EPA (39%) + DHA (26%) [39].…”
Section: Use Of Omega 3 6 and 9 In Brain Ischemia Animal Modelsmentioning
confidence: 99%
“…Preconditioning aims to prepare the host to a future lesion either by decreasing the intensity of its response or by inducing resilience of the organism towards the biological challenge to happen 1 . Various experimental and clinical studies have provided evidence of the preconditioning effects of the dipeptide l-alanyl-glutamine (L-Ala-Gln).…”
Section: Introductionmentioning
confidence: 99%
“…Pinheiro et al 5 investigated the effects of pre-conditioning with mixtures of oils containing high and low ratio ω-6/ω-3 and ω-9/ω-6…”
Section: Introductionmentioning
confidence: 99%